Pemberdayaan Santri Melalui Pelatihan Budidaya Burung Puyuh Petelur di Pondok Pesantren Al Mustaqim Desa Ketindan Kecamatan Lawang Kabupaten Malang - Diannisa, Nabila Amalia; Warnaen, Andi; Nurlaili (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Al Mustaqim Islamic Boarding School has developed a quail egg farming business, but the students' competency in managing it is still limited, so a systematic training model is needed. This study aims to design, implement, and evaluate the effectiveness of a quail egg farming training model based on student empowerment. The study used the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model and a descriptive quantitative approach. The sample was determined saturated, including 13 respondents at the needs analysis stage and 55 participants at the training implementation stage. Data were collected through questionnaires and analyzed using descriptive statistics percentages and the N-Gain test. The results of the needs analysis showed that the training was in the category of very needed (88.14%), supported by the readiness of facilities (76.92%) and the Islamic boarding school environment (85.90%). The developed training module was declared very feasible based on validation by material experts (77.27%) and media experts (97.91%). The training implementation resulted in increased knowledge (N-Gain 93.86%; effective category), skills (84.91%; effective), and attitudes (60.40%; quite effective), with the training model being rated as very good (89.43–94.09%). The developed training model was proven to be valid and effective in improving the competency of students, and can be an alternative empowerment program that supports the development of Islamic boarding school-based entrepreneurship and more sustainable business unit management.